AVALIAÇÃO PRECOCE DA CICATRIZ DE CESAREA. INFLUÊNCIA DO FIO FARPADO NAS CARACTERÍSTICAS ULTRASSONOGRÁFICAS DO NICHE - Newton de Paula Ishikawa (2025)
The pathophysiology of post-cesarean uterine scar defect has yet to be fully elucidated. This study investigated the hypothesis of extreme precocity of hysterorrhaphy dehiscence as an initial stage of isthmocele and the influence of barbed or polyglactin sutures in this process. A longitudinal, prospective, randomized, double-blind study was conducted from February 2023 to February 2024 at the Hospital Universitário Maria Aparecida Pedrossian (HUMAP-EBSERH), a teaching hospital in Campo Grande, Mato Grosso do Sul state, Brazil. Eighty-three pregnant women with no history of cesarean section were enrolled and assigned to one of two groups (suturing with #0 polyglactin group or suturing with #1 barbed PDS thread group) at a 1:1 ratio. In both suture groups, hysterorrhaphies were continuous, unlocked, involved the entire myometrium in a single layer, and included the endometrium. Transvaginal ultrasonography (TVUSG) and three-dimensional transvaginal ultrasonography (3D-TVUSG) were performed on the second day postpartum to investigate the presence of scar dehiscence and measure its maximal width. A second ultrasound examination, employing TVUSG, 3D-TVUSG, saline infusion sonohysterography (SIS), and 3D saline infusion sonohysterography (3D-SIS), was performed 45-55 days after delivery (late puerperium) to investigate the occurrence of isthmocele and measure its dimensions. Only 33 women in the barbed-thread group and 37 in the polyglactin group underwent the second examination. Subject age ranged from 18 to 37 (25.43±0.62) years. The groups were homogeneous for clinical characteristics, except for the integrity of amniotic membranes, which were more preserved in the barbed-suture group (p = 0.04). In the late puerperium, the barbed-thread group exhibited lower rates of isthmocele formation, regardless of ultrasound technique adopted (TVUSG: p = 0.039; 3D-TVUSG: p = 0.011; SIS: p = 0.009; 3D-SIS: p = 0.029). In the early puerperium, dehiscence was observed in 72.9% of subjects (51), with maximal mean width of 0.40 ± 0.04 mm and no group difference. Similarly, no difference was observed for suture types in the progression of the healing defect between early and late puerperium. In the late puerperium, barbed-thread sutures yielded better results than polyglactin in terms of the incidence of isthmocele, but not for large defects, irrespective of ultrasound technique. 3D-SIS proved highly effective as a tool for evaluating this uterine alteration. Keywords: Cesarean section. Cesarean scar defect. Isthmocele. Barbed suture. Uterine closure. 3D ultrasonography.